Acute pancreatitis complicated by hemolytic uremic syndrome: a pediatric case - Sevgin Taner; Işıl Ezel Taşkın Karaçay; İlknur Arslan (SpringerOpen, 2022)
Abstract Background Hemolytic uremic syndrome (HUS) is characterized by microangiopathic hemolytic anemia (MAHA), thrombocytopenia, and acute kidney injury. The acute pancreatitis-associated HUS is a rare entity, and this case is one of the few pediatric cases reported. Case presentation A 17-year-old girl referred to the emergency department with complaints of abdominal pain, fever, and vomiting. The skin and sclera were icteric. Murphy's sign was positive. Hemogram was normal, biochemical analysis revealed an increase in liver function tests and cholestasis enzymes. Abdominal CT revealed multiple stones in the hydropic gallbladder lumen and the pancreas was edematous. With a diagnosis of acute pancreatitis supportive treatment was started. Acute kidney failure, cholestasis, anemia, and thrombocytopenia developed at the 2nd day of follow-up. Thrombotic thrombocytopenic purpura was excluded with normal ADAMTS-13 level. Intermittent hemodialysis and plasma exchange (PE) treatments were initiated, considering pancreatitis-related HUS. On the 3rd day of PE, the patient's urine output exceeded 1 cc/kg per hour. No schistocyte was found in the peripheral smear after 7 PE and 5 hemodialysis sessions. Anemia, thrombocytopenia, and kidney functions improved. On the 15th day of the follow-up, endoscopic retrograde cholangiopancreatography performed, and gallbladder stones were removed. Conclusion The pathogenesis of HUS developing after acute pancreatitis is not fully understood. The mechanism proposed is that acute pancreatitis triggers cytokine release, resulting in endothelial damage and HUS. In conclusion, HUS may rarely develop in patients with acute pancreatitis. With the early diagnosis and appropriate treatment, the kidney functions can be completely normalized.